Fine-tuning immunity: ubiquitin-dependent regulation of interleukin-17A expression by Th17 cells - Raj, Desh; Verma, Amit K.; Mathur, Risha; Woody, Jenna; Kathania, Mahesh; Venuprasad, K. (Frontiers in Immunology, 2025)
Interleukin-17A (IL-17A) is a pro-inflammatory cytokine that plays a pivotal role in immune responses, particularly in the pathogenesis of various autoimmune diseases and infections. Recent advances have highlighted the significance of post-translational modifications, particularly ubiquitination, in regulating IL-17A expression and IL-17A receptor signaling pathways. Here, we summarize the intricate relationship between IL-17A and ubiquitination, exploring how ubiquitin-mediated processes influence IL-17A production, receptor signaling, and downstream effector functions. We provide insights into the potential therapeutic implications of targeting IL-17A and its ubiquitination pathways in inflammatory diseases and autoimmune disorders. A clear understanding of this relationship could pave the way for novel strategies in immune modulation, potentially enhancing management and treatment efficacy in various human diseases.